Research on Gas Flow Characteristics in Capillary Tube - Feng Lifeng; Huang Xiaofeng; Yan Zhiheng (Zhileng xuebao)
Energy loss for a gas flowing inside a capillary tube was obtained experimentally. With data processing, the curves of the gas flow rate change with different lengths and inner diameters for the capillary tube were achieved. The gas flow rate change curves inside the capillary tube with the pressure difference were imitated.